PERLINDUNGAN HUKUM TERHADAP KONSUMEN TRANSPORTASI BERBASIS ONLINE YANG MENGGUNAKAN DRIVER CADANGAN - Stefani Erlina Halim; Siti Nurbaiti (Fakultas Hukum Universitas Tarumanagara, 2018)
Logistic or transportation, including online transportation is an essential aspect in every day’s life. Technology advancement has promoted the introduction of online transportation in Indonesia. However, there is no clear integrated regulation of online transportation including reserve driver. This research also to look at how online transportation company will be responsible on the consumer who used the service of ‘backup’ driver; and what is the legal protection of the consumer in order to protect consumer who had used the service of reserve driver. The method used in this research is normative research specifications, using secondary data and primary data as supporting data with the law approach. The result shows that online transportation customers with reserve driver cannot hold accountability to the online transportation company based on Article 19 of the UUPK and Article 192 UULLAJ, because the business owners are not public transport companies but are the application-based companies. In addition, online transportation also does not provide legal protection to passengers, including of reserve driver, consumers cannot sue the company under UUPK or UULLAJ, but consumers can sue the company under Article 1365 of the Civil Code. Hence, author suggests the government should issue a government-controlled regulation regarding online transportation including reserve driver which could result in the provisions usage of the carrier responsibility in accordance to the UULLAJ by online transportation. Furthermore, online transportation company must provide legal protection to ensure legal certainty for consumers by releasing regulations and sanctions for drivers who lend their account to other driver.